Studi Deskriptif Penanaman Karakter Disiplin Melalui Ekstrakurikuler Musik Dol di SDN 36 Kota Bengkulu - Syafitri, Rani; Tarmizi, Pebrian; Ariffiando, Nady Febri (Universitas Bengkulu, 2024)
This study aims to describe the inculcation of the character of discipline through dol music extracurriculars and governance management at SDN 36 Bengkulu City. Using a type of qualitative research with a descriptive approach. The research subjects were school principals, administration staff, extracurricular trainers, students, and dol music experts. Observation data collection techniques, interviews, and documentation. Data were analyzed through data collection, data reduction, data presentation, and drawing conclusions. Test the validity of the data using technique and source triangulation. The results of the study show that in the implementation of the cultivation of disciplinary character through extracurricular music dol is carried out using teaching methods, exemplary and gradual habituation through the process of moral knowing, moral feeling, and moral action, in participating in extracurricular activities students have discipline which includes being on time, being able to estimate time to complete something, use objects according to their function, comply with agreed rules, orderly in waiting their turn, and have a record of attendance, but there are still students who are less disciplined in taking and returning objects to their place. With a governance management system that is already running in accordance with the rules starting from planning, organizing, implementing and evaluating. However, in the planning stage, operational standards have not been prepared, clear organizational structure for activities has not been prepared, in the organizing stage, there has been no separate honorarium for extracurricular trainers, and letters for coordination meetings are no longer used.